Design of software defined radio of ground station for receiving NANO-satellites image data in S-band - Baktybekov, K.S.; Bochkova, E.N.; Bochkova, E.N.; Korol, V.V.; Murushkin, М.S.; Zhumazhanov, B.R. (Eurasian Physical Technical Journal, 2024)
This paper presents results for design, production and implementation of a ground station for transmitting and receiving information in the S-band for low-orbital nanosatellites for remote sensing of the Earth. A distinctive feature of the solution is that it uses universal low-cost Software Defined Radio hardware platforms based on programmable logic arrays and transceivers, such as the AD9361. Computational resources are saved by usage of a FIR filter with real coefficients and a carrier signal with a symmetrical impulse response, as well as a frequency converter using the CORDIC algorithm, which provides an efficient solution in terms of field programmable gate arrays resources. This work computes total and useful data transfer rates, as well as the required ratio of the energy of one message bit to the value of the power spectral density of the equivalent noise when used for encoding and modulation of a standard DVB-S2 MODCOD signal. Evaluation of the parameters of the Software Defined Radio field programmable gate arrays transceiver showed that it can be used in both the S and X frequency bands without significant changes in hardware, which can significantly reduce the cost of the ground station.
Keywords: ground station; software defined radio; nanosatellite; satellite antenna; field programmable gate arrays; coding; modulation; line communication